Use of superfluid helium to observe directionality of galactic dark matter - Seidel, George M.; Enss, Christian (Journal of low temperature physics, 2024)
The quasiparticle propagation away from the track of a highly ionizing particle in superfluid helium at low temperatures has previously been shown to exhibit anisotropy. We discuss the mechanism responsible for this behavior and show that it occurs for nuclear scattering by dark matter for recoil energies down to a few keV, and perhaps lower. This directionality makes it possible to search for and distinguish galactic dark matter with interaction cross sections that reach into the neutrino fog where coherent neutrino-nucleus scattering presents an irreducible background.